Determination of Fumonisin B1 and B2 in Corn Using Matrix-Phase Dispersion Coupled to High Performance Liquid Chromatography - Ye, Huochun; Lai, Xianwen; Liu, Chenglan (Asian Journal of Chemistry, 2013)
A simple, rapid and reproducible analytical method for the determination of fumonisin B1 (FB1) and fumonisin B2 (FB2) in corn samples by matrix solid-phase dispersion procedure coupled to high performance liquid chromatography (HPLC) with photo-diode array detector (DAD). Several dispersants, eluents and ratios were tested during the optimization of the process in order to obtain the best results. Finally, samples were blended with C18 and the mycotoxins were extracted with 10 mL of 10 mM formic acid in methanol. Analyses were performed by HPLC-DAD. The mobile phase was a mixture of a 77 % methanol and 23 % 0.1 M NaH2PO4 (pH 3.2) solution at 1 mL min-1. The wavelength of detection was 335 nm. The recoveries of the extraction process ranged from 71.0 to 119.7 % with relative standard deviation lower than 15.7 % in all cases, when samples were fortified at three different concentration levels. Limits of detection and quantification were 0.05, 1 and 0.2, 2.0 μg g-1, respectively. Application of the method to the analysis of 13 samples including, corn kernel, flour, corn starch, popcorn, purchased in local supermarkets in Guangzhou city, China, revealed FB1 and FB2 levels.